TAM: Acceptance of E-Learning Technology to Students in Masters of Management Learning - Khoiruddin, Mochammad; Wahyuningsih, Sri Handari; Nuryakin, Nuryakin (Interdisciplinary Social Studies, 2022)
This study aims to evaluate the relationship between technology acceptance factors and online learning for Master of Management students at University Muhammadiyah Yogyakarta in terms of perceived usefulness, perceived convenience, subjective norms, attitudes towards use and behavioral intentions. The object used in this research sample is a master of management student. The sample of this study consisted of 140 respondents who were selected by the sampling method. The data analysis technique used in this study was using Structural Equation Modeling (SEM) with the help of AMOS 23 software. Analysis of the quality testing of the data instrument in this study used validity tests, reliability tests. The results showed that perceived usefulness had a significant effect on usage attitudes, usage attitudes had a significant effect on behavioral intentions, perceived usefulness had a significant effect on perceived convenience, perceived ease of use had a significant effect on usage attitudes, perceived usefulness had a significant influence on subjective norms, norms subjective does not have a significant effect on attitudes to use, subjective norms have no significant effect on behavioral intentions.